WAKTU OPTIMUM PRODUKSI DAN KONSUMSI OKSIGEN RUMPUT LAUT GRACILARIA VERRUCOSA - Kartono, Kartono; Izzati, Munifatul Izzati (MATEMATIKA, 2010)
Seaweed Gracilaria verrucosa not only produce oxygen but also consume oxygen. ConsiderÂ Â the production and consumption of the oxygen, we can determined that the production and consumption models of oxygen like a logistic models. Finally, in this paper Â presented a role to determine an optimum time of the oxygen production and consumption.